Representasi Perempuan dalam Iklan Sunsilk Hijab Anti Ketombe: Analisis Wacana Kritis Sara Mills - Cintya Ratnaduhita; Diah Ariani Arimbi; Nunuk Endah Srimulyani (School of Communication Science and Media Business, 2025)
This study aims to reveal the representation of women in the Sunsilk Hijab Anti-Dandruff advertisement using a descriptive qualitative approach and Sara Mills’ critical discourse analysis theory. The focus of this research includes the position of the subject, object, and reader within the advertisement discourse, as well as how language and visuals construct the image of women. The research data consists of a video advertisement for Sunsilk Hijab Anti-Dandruff obtained from the official YouTube channel of Sunsilk Indonesia. Data collection techniques were carried out through observation, which involved watching, recording, and identifying relevant visual and verbal elements. Data analysis uses Sara Mills’ theory by examining the relationship between text and image to uncover the embedded ideological meanings. The findings show that the advertisement represents hijab-wearing women as active subjects who remain dynamic despite experiencing dandruff problems. Sunsilk is positioned as a solution that respects their identity and provides comfort. The reader is positioned as an individual seeking practical solutions to dandruff issues, particularly for hijab-wearing women. In conclusion, the advertisement not only offers a product but also constructs a discourse on the roles and identities of hijab-wearing women in public spaces, while building the image of modern women who remain active, clean, and confident.